The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1098/rsbl.2018.0082
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and socioeconomics in the city: a review of the luxury effect

Abstract: The ecological dynamics of cities are influenced not only by geophysical and biological factors, but also by aspects of human society. In cities around the world, a pattern of higher biodiversity in affluent neighbourhoods has been termed ‘the luxury effect'. The luxury effect has been found globally regarding plant diversity and canopy or vegetative cover. Fewer studies have considered the luxury effect and animals, yet it has been recognized in the distributions of birds, bats, lizards and indoor arthropods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(153 citation statements)
references
References 60 publications
(122 reference statements)
7
126
1
1
Order By: Relevance
“…Attributes like income, ethnicity, and education have been shown to be the primary drivers of these landscape choices across multiple studies (Larsen and Harlan 2006, Larson et al 2009, Zhou et al 2009, Mel endez-Ackerman et al 2014. For instance, residents in wealthier portions of Phoenix and many other cities have greater access to diverse communities of regionally distinctive bird species (Hope et al 2003, Kinzig et al 2005, Lerman and Warren 2011, Leong et al 2018. Our previous studies in Phoenix also found increased satisfaction of residents in neighborhoods with greater desert bird diversity (Lerman and Warren 2011).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Attributes like income, ethnicity, and education have been shown to be the primary drivers of these landscape choices across multiple studies (Larsen and Harlan 2006, Larson et al 2009, Zhou et al 2009, Mel endez-Ackerman et al 2014. For instance, residents in wealthier portions of Phoenix and many other cities have greater access to diverse communities of regionally distinctive bird species (Hope et al 2003, Kinzig et al 2005, Lerman and Warren 2011, Leong et al 2018. Our previous studies in Phoenix also found increased satisfaction of residents in neighborhoods with greater desert bird diversity (Lerman and Warren 2011).…”
Section: Introductionmentioning
confidence: 81%
“…, Leong et al. ). General patterns emerging suggest that the inequalities to access fall along economic lines, whereby higher income sections of cities support higher species diversity (Hope et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the main mechanisms proposed to explain the Luxury Effect are: a greater investment in management of vegetation (both public and private) in richer areas; and, a greater demand for housing in greener and more biodiverse areas which thus increases property prices (Leong et al, 2018). These are not mutually exclusive.…”
Section: Mcgarry 2008) Within South Africa There Is Support For a mentioning
confidence: 99%